The Effect of Leverage and Capital Intensity on Tax Avoidance with Independent Commissioners as a Moderating Variable (Proceeding of the International Conference on Economics, Accounting, and Taxation, 2025)
This study aims to examine the effect of Leverage and capital intensity on tax avoidance with independent commissioners as a moderating variable in property and real estate companies listed on the Indonesia Stock Exchange (IDX). Tax avoidance practices in this sector are considered relatively high due to the complexity of fixed asset management and financing structures. The study applies a quantitative approach with an associative method and purposive sampling, resulting in 21 companies as the final sample with a total of 105 observations during the 2020–2024 period. Data were analyzed using multiple linear regression and Moderated Regression Analysis (MRA) with SPSS version 25. The results show that leverage has a positive and significant effect on tax avoidance, indicating that a higher level of debt usage increases the likelihood of tax avoidance through interest expenses. Capital intensity also has a positive and significant effect on tax avoidance, as higher investment in fixed assets provides opportunities for firms to utilize depreciation expenses in reducing taxable income. The moderating test reveals that independent commissioners do not moderate the relationship between leverage and tax avoidance but significantly moderate the relationship between capital intensity and tax avoidance in a negative direction, thereby weakening the effect. These findings highlight the importance of corporate governance mechanisms through the presence of independent commissioners in mitigating tax avoidance, although their effectiveness remains limited to specific aspects. This study contributes empirically to the taxation and corporate governance literature and provides recommendations for regulators and tax authorities in strengthening tax compliance monitoring in the property sector.